2022
DOI: 10.3390/mi13060863
|View full text |Cite
|
Sign up to set email alerts
|

Fully Integrated High-Performance MEMS Energy Harvester for Mechanical and Contactless Magnetic Excitation in Resonance and at Low Frequencies

Abstract: Energy harvesting and storage is highly demanded to enhance the lifetime of autonomous systems, such as IoT sensor nodes, avoiding costly and time-consuming battery replacement. However, cost efficient and small-scale energy harvesting systems with reasonable power output are still subjects of current development. In this work, we present a mechanically and magnetically excitable MEMS vibrational piezoelectric energy harvester featuring wafer-level integrated rare-earth micromagnets. The latter enable harvesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Furthermore, this has also been proven in integrated circuits and microelectromechanical systems (MEMS) [269,270] . Nanotechnology combined with MEMS has been widely used in optical devices [271,272] , portable electronic devices [273] , and energy [274,275] , leading to the development of new devices such as zero-power sensors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this has also been proven in integrated circuits and microelectromechanical systems (MEMS) [269,270] . Nanotechnology combined with MEMS has been widely used in optical devices [271,272] , portable electronic devices [273] , and energy [274,275] , leading to the development of new devices such as zero-power sensors.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve a stable vacuum inside the porous microstructure, films having a thickness of several micrometers can be deposited by standard MEMS chemical and physical vapor deposition processes. It has already been shown that, for example, silicon oxide can be deposited pinhole-free by PECVD on top of a porous 3D microstructure [ 19 , 21 ]. However, the (long-term) hermeticity of such sealings remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the wafers are cleaned of any unwanted powder residues and are ready for further processing under standard MEMS cleanroom conditions. In previous work, the use of PowderMEMS structures for energy harvesting and zero-powder wakeup [ 18 , 19 ], permanent micromagnets and magnetic position detection [ 20 , 21 ], and the creation of liquid-cooled microscale inductor cores [ 22 ] has been presented.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic plucking principle has also been applied in electromagnetic [77] and mixed piezo-magnetic transduction [136], leading to patented ideas as well [137,138]. Additionally, Bodduluri et al [139] implemented magnetic plucking at the MEMS scale with an integrated process of the magnetic material deposition. [125] with the permission of Elsevier.…”
Section: Magnetic Interaction Broadband and Plucking Mechanismsmentioning
confidence: 99%